2005
DOI: 10.1128/iai.73.1.378-384.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Helicobacter pylori Thiol Peroxidase Bacterioferritin Comigratory Protein to Oxidative Stress Resistance and Host Colonization

Abstract: Peroxiredoxins, the enzymes that catalyze the reduction of hydrogen peroxide and organic hydroperoxides, are ubiquitous proteins that protect organisms from damage by reactive oxygen species. Helicobacter pylori contains three members of the peroxiredoxin family: AhpC (alkyl hydroperoxide reductase), Tpx (thiol-specific peroxidase), and bacterioferritin comigratory protein (BCP). In this study, we characterized H. pylori bcp mutant strains and wild-type BCP. Compared to the parent strain and the ahpC mutant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 28 publications
1
93
0
Order By: Relevance
“…Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33). The native structure of AhpC in S. typhimurium was shown to exist as a dimer (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33). The native structure of AhpC in S. typhimurium was shown to exist as a dimer (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Alkyl hydroperoxide reductase (AhpC), a thioredoxin (Trx)-dependent AhpC, is a member of the 2-Cys peroxiredoxins family (2-Cys Prxs). A group of thiolspecific antioxidant enzymes, which catalyze the reduction of hydrogen peroxide and organic hydroperoxides, are ubiquitous proteins that protect organisms from damage by reactive oxygen species [15] . H pylori are oxygensensitive microaerophilic bacteria, and contain many antioxidant proteins, among which AhpC is most abundant.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the binding site of E. coli Tpx appears to be optimized for recognition of fatty acid hydroperoxides (22), suggesting that this is a major function of the enzyme. The three Prxs of H. pylori have different substrate preferences: AhpC and Hp-Tpx exhibit broad protective activity against a range of hydroperoxides (9,26), and Bcp has a distinct substrate preference for linoleic acid (103). AhpC from H. pylori and other bacterial species also possess activity against peroxynitrite, which has not been observed for the other enzymes (15).…”
mentioning
confidence: 99%
“…AhpC from H. pylori and other bacterial species also possess activity against peroxynitrite, which has not been observed for the other enzymes (15). The enzymes are distinguished by the number of conserved cysteine residues within the structure, with AhpC classified as a "typical" 2-Cys Prx (78), Hp-Tpx as an "atypical" 2-Cys Prx (70), and Bcp as a 1-Cys Prx (103). Typical and atypical 2-Cys Prxs differ in the conformation of the disulfide bond that forms upon oxidation of the cysteine residues: the disulfide bond of typical 2-Cys Prx is intermolecular, leading to dimer formation, whereas the bond in atypical 2-Cys Prx is intramolecular, resulting in monomer formation (83).…”
mentioning
confidence: 99%